Clinical and Laboratory Development of Echinocandin Resistance in Candida glabrata: Molecular Characterization - Rivero-Menendez, Olga; Navarro-Rodriguez, Patricia; Bernal-Martinez, Leticia; Martin-Cano, Gema; Lopez-Perez, Laura; Sanchez-Romero, Isabel; Perez-Ayala, Ana; Capilla, Javier; Zaragoza, Oscar; Alastruey-Izquierdo, Ana (Frontiers in Microbiology, 2019)
The pathogenic yeast Candida glabrata has become a public health issue due to the increasing number of echinocandin resistant clinical strains reported. In this study, acquisition and development of resistance to this antifungal class were studied in serial C. glabrata isolates from five patients admitted in two Spanish hospitals with a resistant profile against echinocandins associated with different mutations in hot-spot 1 of FKS2 gene. For two of these patients susceptible FKS wild-type isolates obtained prior to resistant ones were also investigated. Isolates were genotyped using multilocus sequence typing and microsatellite length polymorphism techniques, which yielded comparable results. Susceptible and resistant isolates from the same patient had the same genotype, being sequence type (ST) 3 the most prevalent among them. Isolates with different FKS mutations but the same ST were present in the same patient. MSH2 gene alterations were also studied to investigate their correlation with antifungal resistance acquisition but no association was found with antifungal resistance nor with specific genotypes. In vitro exposure to increasing concentrations of micafungin to susceptible isolates developed colonies carrying FKS mutations in agar plates containing a minimum concentration of 0.06 mg/L of micafungin after less than 48 hours of exposure. We investigated the correlation between development of resistance and genotype in a set of susceptible strains after being in vitro exposed to micafungin and anidulafungin but no correlation was found. Mutant prevention concentration values and spontaneous mutation frequencies after selection with both echinocandins were statistically similar, although FKS mutant colonies were more abundant after micafungin exposure (p<0.001). Mutation S663P and F659 deletion were the most common ones found after selection with both echinocandins.